2022
DOI: 10.1155/2022/6182592
|View full text |Cite
|
Sign up to set email alerts
|

A Global and Sector-Based Comparison of OCT Angiography and Visual Field Defects in Glaucoma

Abstract: Purpose. To evaluate the correlation of optical coherence tomography angiography (OCTA) and spectral-domain optical coherence tomography (SD-OCT) with visual field for global and sector-based indices among glaucoma and glaucoma-suspected eyes. Patients and Methods. This is a retrospective study, and in total, 48 glaucoma eyes and 31 glaucoma suspect eyes were included. The correlation between visual field parameters and radial peripapillary capillary (RPC) vessel density via OCTA was compared to the correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…[31][32][33] Evaluation of correlations among vascular perfusion, structural and visual field testing parameters showed that VPD and FI correlated well with OCT-determined mean peri-papillary RNFL thickness, as well as RNFL thickness and in the superior and inferior quadrants, in agreement with previous results. 34 These results were not unexpected because peripapillary RNFL thickness and vascular parameters were measured in similar areas. In contrast, the relationship between vascular parameters and OCT-determined macular GCA was only fair, as these parameters were measured in different anatomical areas.…”
Section: Discussionmentioning
confidence: 66%
“…[31][32][33] Evaluation of correlations among vascular perfusion, structural and visual field testing parameters showed that VPD and FI correlated well with OCT-determined mean peri-papillary RNFL thickness, as well as RNFL thickness and in the superior and inferior quadrants, in agreement with previous results. 34 These results were not unexpected because peripapillary RNFL thickness and vascular parameters were measured in similar areas. In contrast, the relationship between vascular parameters and OCT-determined macular GCA was only fair, as these parameters were measured in different anatomical areas.…”
Section: Discussionmentioning
confidence: 66%